2018
DOI: 10.1371/journal.pone.0191671
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of actual uptake and willingness to use pre-exposure prophylaxis to prevent HIV acquisition among men who have sex with men in Hong Kong, China

Abstract: ObjectivesThis study was to investigate the prevalence of actual uptake of pre-exposure prophylaxis (PrEP), willingness to use daily oral PrEP under two cost scenarios, and potential issues related to PrEP use among men who have sex with men (MSM) with HIV negative/unknown sero-status in Hong Kong, China. Factors associated with the two measures of willingness were also investigated.Methods403 eligible MSM completed the anonymous venue-based face-to-face interview/telephone interview.ResultsOnly 1% had ever us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 36 publications
6
59
0
Order By: Relevance
“…The majority of our survey participants doubted PrEP and only a quarter (26%) selected that they would be willing to take PrEP despite the fact that it is one of the most promising modes of HIV prevention. Most studies in China have focused on rates of PrEP acceptance rather than actual uptake , and while reported levels of PrEP acceptance among Chinese MSM vary widely from 19.1% to 71.3% , uptake has been consistently reported as very low . Compared to younger MSM, our study identified those who were over 40 years old had higher rate of PrEP uptake.…”
Section: Discussionmentioning
confidence: 64%
“…The majority of our survey participants doubted PrEP and only a quarter (26%) selected that they would be willing to take PrEP despite the fact that it is one of the most promising modes of HIV prevention. Most studies in China have focused on rates of PrEP acceptance rather than actual uptake , and while reported levels of PrEP acceptance among Chinese MSM vary widely from 19.1% to 71.3% , uptake has been consistently reported as very low . Compared to younger MSM, our study identified those who were over 40 years old had higher rate of PrEP uptake.…”
Section: Discussionmentioning
confidence: 64%
“…Among GBMSM with experience of SDU in the past year who were not on PrEP, about 70% were willing to use daily PrEP in the next six months. The rate was higher than that of GBMSM in general in Hong Kong (27). Data on willingness to pay suggested that the current market rate for In addition, our study also showed that prevalence of SDU and chemsex among GBMSM in Hong Kong was lower than that of Western Europe, Australia, the United States and mainland China (5,6,(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 49%
“…or "definitely will". Such a definition has been commonly used in previous studies (27,60,61). For those with willingness to use PrEP, they were further asked about the maximum amount (in HK$) they were willing to pay per month for using daily PrEP.…”
Section: Prep Use and Willingness To Use Prepmentioning
confidence: 99%
See 2 more Smart Citations